«Materials on the kyrgyz (kazakh) land use» as the source for economic and economic history of kazakh farms (Journal of history, 2020)
This article analyzes the source called «Materials Kirghiz (Kazakhs) land use...» of the late XIX – early XX century. Topicality of the theme      of investigation is that «Materials on Kyrgyz land using» introduces code of statistical materials which consists of 27 volumes, and it is invaluable source in investigation ethnical history of Kazakh people, peculiarities of Kazakh traditional economy. Informativeness , concentrated in materials is unique. First of all by the scale of covering of all totality of important facts, events, occurrences in the field of history, ethnography studies, ge- ography, toponymy , demography and etc. That’s why nowadays great interest to source study aspect grew in learning given source. The choice of the theme of investigation is explained by its great scientific theoreti- cal significance.   It discusses the methodology of research and analysis   of the important source of Kazakh history «Materials of Kyrgyz land use...», proposed methods of research and testing, classification and analysis in accordance with the science of sources and methods of application in specific historical studies.